Canine therapy as a method of social and psychological rehabilitation for combatants with post-traumatic stress disorder: from basic principles to practical implementations - Safin, Oleksandr; Kravchenko, Oksana (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
Background. Canine therapy is a method that involves sessions with specially trained dogs aimed at correction, rehabilitation, and social adaptation of individuals requiring social and psychological assistance, conducted under the guidance of a qualified canine therapist. It contributes to the enhancement of individual mental health. The understanding of canine therapy is broad. It may involve the use of a dog as a therapeutic tool, a behavioral motivator, or a participant in group psychotherapeutic process. Canine therapy is considered a professional modality that requires specialized training for canine therapists and special training of animals, compliance with safety rules and an ethical code for canine therapists. Studies of foreign and Ukrainian experience indicate that canine therapy is effective in treating post-traumatic stress disorder (PTSD). The aim of this article is to substantiate the psychological foundations of using canine therapy as a method of social and psychological rehabilitation for combatants with PTSD. Methods. Content analysis of scientific sources, comparison, classification, systematization. Results. The implementation of an innovative model of social and psychological rehabilitation of combatants using canine therapy has the following advantages: this process engages nearly all sensory modalities; a positive effect on the overall physiological condition of combatants has been observed, particularly the normalization of blood pressure; therapy dogs can work with military personnel who have sustained severe injuries, have disabilities, or experience limitations in independent mobility or self-care. The systematic functioning of reintegration environment within higher education institutions – as an effective model integrating all stakeholders of social and psychological rehabilitation at the interdepartmental, intersectoral, and interprofessional levels – expands the potential for the social and psychological rehabilitation of combatants and veterans through canine therapy, provided that the conceptual principles of the developed and verified program for the social and psychological rehabilitation of combatants with PTSD using canine therapy are implemented. Conclusions. The developed program for the social and psychological rehabilitation of combatants with PTSD using canine therapy can be applied in rehabilitation and cynological centers, socially oriented institutions working with military personnel with the aim of restoring their psycho-emotional and social functioning, as well as supporting them during the process of adaption to the common conditions of the civilian life.